Participation and empowerment among self-help groups in Kano City - Ibrahim, Abdul-Aziz; Abu Samah, Asnarulkhadi; Saidu, Mohammed Bashir (Universiti Putra Malaysia Press, 2018)
Self-Help Groups (SHGs) are local organisations that create avenues for grassroots participation at the community level in self-help activities. SGHs play an important role in helping people participate in community development activities that eventually lead to empowerment. In line with this, this paper examined the relationship between dimensions of participation and empowerment among SHG members in Kano City, Nigeria. Data were collected using a structured questionnaire from 400 respondents from four local government areas of Kano City. The descriptive analysis showed a high level of participation and empowerment among the respondents. Pearson correlation analysis revealed a significant positive relationship between the dimensions of participation and empowerment. This study supported previous literature on SHG sustainability. Practically, SHG activities have the potential to become a model for sustainable community development projects at the locality level.